Jesus and the Last Supper - Pitre, Brant James (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2015)
Who did Jesus of Nazareth claim to be? What was his relationship with early Judaism? When and how did he expect the kingdom to come? What were his intentions? Though these key questions have been addressed in studies of the historical Jesus, Brant Pitre argues that they cannot be fully answered apart from a careful historical analysis of the Last Supper accounts. In this book Pitre offers a rigorous, up-to-date study of the historical Jesus and the Last Supper, filling a significant gap in current Jesus research. Situating the Last Supper in the triple contexts of ancient Judaism, the life of Jesus, and early Christianity, Pitre brings to light crucial insights into major issues driving the quest for Jesus. His Jesus and the Last Supper is sure to ignite discussion and debate.
Jesus and Judaism -- The self-understanding of Jesus -- The eschatology of Jesus -- Jesus and the early church -- Method of proceeding -- The new Moses -- The new Moses in early Judaism -- The feeding of the multitude -- The Blood of the Covenant -- The new bread of the presence -- The new manna -- The manna in early Judaism -- The Lord's Prayer and the eschatological manna -- The teaching in the synagogue at Capernaum -- The date of the Last supper -- The apparent contradiction -- The Essene hypothesis -- The Johannine hypothesis -- The Synoptic hypothesis -- The Passover hypothesis -- The new Passover -- The Passover in early Judaism -- The temple context of the Last Supper -- The Body and Blood of the Lamb -- The eucharistic restoration of Israel -- The messianic banquet in early Judaism -- Eating and drinking with Abraham, Isaac, and Jacob -- Jesus's vow at the Last supper -- Conclusion.
Includes bibliographical references (pages 518-552) and indexes.
Keywords: Jesus Christ -- Historicity; Jesus Christ -- Jewishness; Lord's Supper; Lord's Supper -- Biblical teaching; Church history -- Primitive and early church, ca. 30-600.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Christianity -- Origin; Christianity; Christianity -- Origin; Church history -- Primitive and early church; Historicity of Jesus Christ; Interfaith relations; Jewishness of Jesus Christ; Judaism; Judaism -- Post-exilic period (Judaism); Lord's Supper; Lord's Supper -- Biblical teaching; 586 B.C. - 600 A.D.; History